2014
DOI: 10.1590/s1808-18512014130400362
|View full text |Cite
|
Sign up to set email alerts
|

Post-laminectomy deformities

Abstract: Objective: To present the deformities and evaluate the results of their treatment. Methods: Retrospective study of patients with deformity following surgical access to the spinal canal. Fifteen patients who met the inclusion criteria were included. Patients without complete data in medical records were excluded. Results: Fourteen patients underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…It has been stated that postoperative immobilization will not prevent the appearance of deformity, but may delay the deformity (5).…”
Section: Resultsmentioning
confidence: 99%
“…It has been stated that postoperative immobilization will not prevent the appearance of deformity, but may delay the deformity (5).…”
Section: Resultsmentioning
confidence: 99%
“…Postlaminectomy deformity when severe may cause neural compression which in turn would lead to neurological symptoms. [6] Robert and Bortolussi postulated that as the deformity progresses, the weight-bearing pivot of the body moves anteriorly and therefore can only be amended with spinal column sagittal balance reconstruction. [7] Some theories propose that radiation and posterior muscle inadequacy leading to arrest in vertebral growth are the primary reasons of deformity postlaminectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Delay in the development of kyphotic deformity can be achieved by immobilization after surgery; however, it does not appear to prevent it. [6] Surgical intervention is indicated in the severity and progression of the deformity and related neurological deficits. [9] Lutz and Munhoz da Rocha reported that the time between surgery and postsurgery kyphosis was 4 years and 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…This may or may not be related to the failure of support of the anterior portion of the spinal column. In its severe form, post-laminectomy deformity may cause neurologic symptoms due to neural compression (1). Bartolussi hypothesized that as the deformity progresses the weight tolerating pivot of the body moves anteriorly and thus can only be corrected with spinal column sagittal balance reconstruction (4).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal kyphotic deformity after spinal laminectomy and laminoplasty is uncommon in adults but often occurs in the pediatric population; it has been reported that spinal deformity occurs in 26% of newborn infants and children after laminectomy (1,2). Lonstein proposed that kyphotic deformity can be attributed to the decrease in cartilage growth and anterior wedging associated with laminectomies in which the cartilage endplates of the vertebral bodies experience increased pressure in the anterior direction (3).…”
Section: Introductionmentioning
confidence: 99%